Catalytic Mechanism of Oxygen Vacancies in Perovskite Oxides for Lithium–Sulfur Batteries. Issue 26 (22nd May 2022) - Hou, Wenshuo; Feng, Pingli; Guo, Xin; Wang, Zhenhua; Bai, Zhe; Bai, Yu; Wang, Guoxiu; Sun, Kening
Abstract: Defective materials have been demonstrated to possess adsorptive and catalytic properties in lithium–sulfur (Li–S) batteries, which can effectively solve the problems of lithium polysulfides (LiPSs) shuttle and sluggish conversion kinetics during charging and discharging of Li–S batteries. However, there is still a lack of research on the quantitative relationship between the defect concentration and the adsorptive‐catalytic performance of the electrode. In this work, perovskites Sr0.9 Ti1− x Mn x O3− δ (STMn x ) ( x  = 0.1–0.3) with different oxygen‐vacancy concentrations are quantitatively regulated as research models. Through a series of tests of the adsorptive property and electrochemical performance, a quantitative relationship between oxygen‐vacancy concentration and adsorptive‐catalytic properties is established. Furthermore, the catalytic mechanism of oxygen vacancies in Li–S batteries is investigated using density functional theory calculations and in situ experiments. The increased oxygen vacancies can effectively increase the binding energy between perovskite and LiPSs, reduce the energy barrier of LiPSs decomposition reaction, and promote LiPSs conversion reaction kinetics. Therefore, the perovskite STMn0.3  with high oxygen‐vacancy concentrations exhibits excellent LiPSs adsorptive and catalytic properties, realizing high‐efficiency Li–S batteries. This work is helpful to realize the application of the quantitative regulation strategy of defect engineering in Li–S batteries. Abstract : Compared with the perovskite Sr0.9 TiO3−δ, the perovskite Sr0.9 Ti0.7 Mn0.3 O3− δ (STMn0.3 ) with a higher concentration of oxygen vacancies exhibits superior adsorptive‐catalytic performance of lithium polysulfides, and improves the utilization of sulfur. The STMn0.3 battery still delivers a superior initial specific capacity of 780 mAh g −1  and a decay rate of 0.032% per cycle after 1500 cycles at 2 C, enabling a high‐efficiency lithium–sulfur battery.